Teenage pregnancy and marital status - Khalid, S; Mohd, TAMT; Hassanah, K; Mokhtar, RH; Masri, MA; Aris, MSM; Sivapatham, L; Ganesalingam, M; Deraman, MRW; Razi, NAM (Wiley-Blackwell, 2024)
Indexed by WOS